Prophylactic use of amantadine in a boarding school outbreak of influenza A - Davies, Joan R. (1988)
Amantadine was used in a boarding school to control an outbreak of influenza A H3N2. Of 859 pupils 79% took amantadine and almost all of them completed the course (100 mg per day for 15 days). While amantadine was being taken the number of clinical cases of influenza was considerably fewer than that predicted on the basis of previous outbreaks of influenza A at the school. However, during the month following the course of amantadine, the outbreak continued with many clinical cases confirmed by virus isolation. The advantages and limitations of amantadine prophylaxis are discussed.